Mixed-Grass Vegetation Response to an Extreme Wildfire Event - Keith Harmoney; Jacob Hadle (Kansas Agricultural Experiment Station Research Reports, 2024)
The wildfires of the 2021-2022 dormant season in Ellis, Osborne, Rooks, and Russell counties occurred under extreme weather conditions. However, most every dormant season contains conditions suitable for wildfires to occur: dried vegetation, low humidity, and potential for days of elevated temperatures and winds. A portion of the 122,000-acre area that burned in the December 2021 Four County Fire also burned in March 2017 during the dormant season. Dormant-season wildfire removes beneficial vegetative soil cover during the dormant season, and has ecological and financial impacts in the following growing seasons. Prior published dormant-season wildfire data showed that yield reductions the growing season after the fire ranged from 25% to 65%, depending on the time, location, and the main grass species consumed in the fire. Less soil cover and less production in the years after the fire may require lower stocking rates, which ultimately results in lower potential income. The Four County Fire burned approximately 12% of the range and pasture acres in these four counties. Therefore, fires of this magnitude have significant ecological and financial impacts on regional communities. To date, only a few historic wildfires in northwest Kansas have data available regarding rangeland response to those wildfires. This study was designed to provide producers with information for ecological and grazing animal planning for the years following dormant season wildfires in western Kansas.
Keywords: backfire; bluestem; dormant season; foliar cover; forage yield; headfire; soil cover